Cheetah Reintroduction in India: Review of Eco-restoration Policy Gaps - (:unkn) unknown (My University, 2024)
Recent Introduction of the African Cheetah in India is more emotion than ecology. These are still kept in the enclosure, and served meat than let them hunt. We find following gap in this inter-continental animal transfer- 1) Cheetah mainly dwell or hunt in the plains savanna habitat and not hill forests of the Kuno National Park (KNP), 2) Cheetah mainly hunt on antelopes (weight< 50 kg) that are rare at Kuno and not on Chital (Spotted deer, weight > 60 kg) prevailing at Kuno, 3) Hares, Pigs and small livestock such as sheep, goat make 30% the Cheetah diet in Africa but ignored/ excluded at Kuno, making it unviable. The imported Cheetah yet await release into the wild due to the risk of prey deficit, pathogens and depredation by Tiger, Leopard, Hyena etc. About 8 i.e. 40% of the 20 Cheetah imported have died, similar to the translocations success rate within Africa. We suggest (1) exploring grassland prevalent sanctuaries in Gujarat-Rajasthan states (2) release Chinkara (Indian Gazelle), pigs, barking deer, wild boars and hares as prey in the wildlife reserve, not just Chital, (3) permit low human disturbance and grasslands in KP & surroundings, including livestock, (4) develop Savanna corridors and network management of wildlife reserves adjoining Kuno (Madhav, Gandhisagar, Ranthambor, Kailadevi) or farther (Tal Chhaper WLS, Churu district & Jaroda closed area, Nagaur district) as the later report multiple times antelope density than KNP.
Keywords: African Research